Hysteretic stressing state features of RCB shear walls revealed by structural stressing state theory - Yan Zhao; Bai Liu; Huaming Li; Hongbo Liu; Guangchun Zhou (Case Studies in Construction Materials, 2021)
This study reveals the essential stressing state features of reinforced concrete block (RCB) shear walls in their hysteretic working process by applying structural stressing state theory and method. The experimental strains of the RCB shear wall are transferred into generalized strain energy density (GSED) values to build the stressing state mode and the parameter characterizing the mode. Then, the Mann-Kendall criterion is used to detect the mutation feature in the evolution of the stressing state characteristic parameter with the hysteretic load increase. Correspondingly, it is verified that the stressing state mode also presents the mutation feature. The stressing state mutation is the essential feature in the structural working process as structural failure starting point, which is the embodiment of the natural law from quantitative change to qualitative change of a system. Furthermore, the stressing state analysis reveals the elastic-plastic branch point in the working process of the RCB shear wall, which could be directly taken as the design point. In total, this study explores a new way to analyze the structural hysteretic working behavior and provides the rational reference to improve the existing design code.